1996
DOI: 10.1086/176998
|View full text |Cite
|
Sign up to set email alerts
|

Very High Energy Gamma-Ray Emission from the Blazar Markarian 421

Abstract: Very high energy gamma-ray emission from the BL Lac object Markarian 421 has been detected over three observing seasons on 59 nights between April 1992 and June 1994 with the Whipple 10-meter imaging Cherenkov telescope. During its initial detection in 1992, its flux above 500 GeV was 1.6$\times$10$^{-11}$photons cm$^{-2}$ s$^{-1}$. Observations in 1993 confirmed this level of emission. For observations made between December 1993 and April 1994, its intensity was a factor of 2.2$\pm$0.5 lower. Observations on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Publicly available lightcurve data from 1992 until today were collected from the Whipple (Kerrick et al 1995;Schubnell et al 1996;Buckley et al 1996;Maraschi et al 1999a), HEGRA (Aharonian et al 1999b,a;Krawczynski et al 2001b;Aharonian et al 2001Aharonian et al , 2002Aharonian et al , 2003Aharonian et al , 2004Kestel 2002), CAT (Piron 2000;Piron et al 2001), HESS (Aharonian et al 2005(Aharonian et al , 2006, MAGIC (Albert et al 2008a;Donnarumma et al 2009), and VERITAS (Rebillot et al 2006;Donnarumma et al 2009) experiments. We are also working on collecting more data from these and other experiments such as the Crimean GT-48 Cherenkov telescope (e.g.…”
Section: Lightcurve Datamentioning
confidence: 99%
“…Publicly available lightcurve data from 1992 until today were collected from the Whipple (Kerrick et al 1995;Schubnell et al 1996;Buckley et al 1996;Maraschi et al 1999a), HEGRA (Aharonian et al 1999b,a;Krawczynski et al 2001b;Aharonian et al 2001Aharonian et al , 2002Aharonian et al , 2003Aharonian et al , 2004Kestel 2002), CAT (Piron 2000;Piron et al 2001), HESS (Aharonian et al 2005(Aharonian et al , 2006, MAGIC (Albert et al 2008a;Donnarumma et al 2009), and VERITAS (Rebillot et al 2006;Donnarumma et al 2009) experiments. We are also working on collecting more data from these and other experiments such as the Crimean GT-48 Cherenkov telescope (e.g.…”
Section: Lightcurve Datamentioning
confidence: 99%
“…Two sources from the B2 sample which were not included by Parma et al (1987) are particularly important to the present analysis: 1101+38 (Markarian 421) and 1652+39 (Markarian 501). These are both classified as BL Lac objects, have very bright radio cores and show blazar characteristics from radio to high‐energy γ‐ray wavebands (Quinn et al 1996; Schubnell et al 1996). They are thought to be examples of the (rare) class of end‐on sources, and their extreme core and jet properties set important constraints on the parameters of relativistic jet models.…”
Section: Data and Observational Parametersmentioning
confidence: 99%
“…Schubnell et al 1996;Petry et al 1996). Our data and analysis of the optical behaviour of Mrk 421 are presented by Tosti et al (1998a) and hence only the light curve is shown (Fig.…”
Section: Mrk 421mentioning
confidence: 99%